The Old Testament in the life of God's people essays in honor of Elmer A. Martens - Isaak, Jon M. 1960-; Martens, Elmer A. 1930- (Winona Lake, Ind. Eisenbrauns, 2009)
Elmer A. Martens: a biographical sketch -- Phyllis Martens -- Abbreviations -- Publications by Elmer A. Martens -- Embracing the law: a biblical theological perspective / Elmer A. Martens -- God's design and postmodernism: recent approaches to Old Testament theology / Paul R. House -- Educating to become wise: intercultural theological education / Marlene Enns -- To know or not to know: Hosea's use of ydo/dot / Douglas Carew -- The problem of preaching the Old Testament / Franklyn L. Jost -- On truth-telling and biblical theology / Rolf P. Knierim -- Yahweh, justice, and religious pluralism in the Old Testament / Elmer A. Martens -- Creation and peace: creator and creature in Genesis 1-11 / Ben C. Ollenburger -- Jethro in the structure of the book of Exodus / Waldemar Janzen -- The case of the Venus Flytrap: the argument of the book of Job / Pierre Gilbert -- Church of justice / Alfred Neufeld -- Righteousness in Romans: the political subtext of Paul's letter / John E. Toews -- O land, land, land: reading the earth story in both Testaments / Elmer A. Martens -- Israel and its land in biblical perspective / Walter C. Kaiser Jr -- God's design and the church / Timothy J. Geddert -- Biblical perspectives on biodiversity: a conversation with E. O. Wilson / Theodore Hiebert -- All creatures great and small: recovering a deuteronomic theology of animals / Daniel I. Block -- The word made bitter: at the table with Joshua, Buber, and Bakhtin / Gordon H. Matties
Addressing the issue of land in the life of God's people. O land, land, land: reading the earth story in both Testaments Elmer A. Martens ; Israel and its land in biblical perspective / Walter C. Kaiser Jr. ; God's design and the church / Timothy J. Geddert ; Biblical perspectives on biodiversity: a conversation with E. O. Wilson / Theodore Hiebert ; All creatures great and small: recovering a deuteronomic theology of animals / Daniel I. Block ; The word made bitter: at the table with Joshua, Buber, and Bakhtin / Gordon H. Matties.
Includes bibliographical references and indexes
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Use; Bible -- Relation to the Old Testament; Bible -- Criticism, interpretation, etc; Bible -- Use; Bible -- Relation to the Old Testament; Justice -- Biblical teaching; Nature -- Religious aspects; Earth in the Bible; Justice -- Biblical teaching; Nature in the Bible; Nature -- Religious aspects; Earth (Planet) -- In the Bible; Festschrift; Aufsatzsammlung